UPAYA INTERNATIONAL MARITIME ORGANIZATION (IMO) DALAM MENGATASI PENDAMPARAN PELAUT SELAMA PANDEMI COVID-19 TAHUN 2020 - Haura Zhafirah Maharani, (2023)
This study aim to discuss the efforts of the International Maritime Organization (IMO) in dealing with the hundreds of thousands stranded seafarers during the COVID-19 pandemic in 2020 by applying the theory of human security, international organization and the maritime legal and regulatory framework. The method used is descriptive qualitative. Sources of data in the form of primary data and secondary data. Data collection techniques used in this study are observation, interview and documentation. Researcher uses three stages of data analysis according to Miles and Huberman (1992), namely, data reduction, data presentation, and withdrawal/verification by data triangulation. The final results of this study show that hundreds of thousands individual global seafarers experience in humanitarian crisis because detention to not exchange workers and force them to continue working on ships causes physical and mental fatigue to the risk of worker accidents and detention unable to receive emergency medical access are series of deviations from the conception of human security. Therefore, as an International Maritime Organization, IMO (International Maritime Organization) seeks to address the problem with various efforts, such as assigns key workers to seafarers, recommends guidelines for worker exchange during the COVID-19 pandemic, urges Member States to implement recommendations, issue Circular Letters, forms the Maritime Safety Committee (MSC) and issues resolutions, collaborates with international organizations and simultaneously voiced the urgent concern of stranded seafarers during the COVID-19 pandemic, such as forcing priority vaccination for seafarers at the United Nations General Assembly (UNGA), publishes the results of a press conference, and forms a special team Seafarer Crisis Action Team (SCAT).